Wearable Electronics Based on Stretchable Organic Semiconductors - Xu, Xinzhao; Zhao, Yan; Liu, Yunqi (Small (Weinheim an der Bergstrasse, Germany), 2023)
Wearable electronics are attracting increasing interest due to the emerging Internet of Things (IoT). Compared to their inorganic counterparts, stretchable organic semiconductors (SOSs) are promising candidates for wearable electronics due to their excellent properties, including light weight, stretchability, dissolubility, compatibility with flexible substrates, easy tuning of electrical properties, low cost, and low temperature solution processability for large‐area printing. Considerable efforts have been dedicated to the fabrication of SOS‐based wearable electronics and their potential applications in various areas, including chemical sensors, organic light emitting diodes (OLEDs), organic photodiodes (OPDs), and organic photovoltaics (OPVs), have been demonstrated. In this review, some recent advances of SOS‐based wearable electronics based on the classification by device functionality and potential applications are presented. In addition, a conclusion and potential challenges for further development of SOS‐based wearable electronics are also discussed. Recent years have witnessed the rapid development of wearable electronics. Stretchable organic semiconductors (SOS) are ideal candidates for the next generation wearable electronics. In this review, some recent advances of SOS‐based wearable electronics are presented and classified based on their functionalities and potential applications. The potential challenges and opportunities for their future development are also discussed.